TRITINA IN MONROE CURTIS BERDSLEY AESTHETIC STUDIES - Narayanasandhy, I Wayan M. Dhamma (Sembadra, Journal of Arts and Education Studies, 2020)
In every work of music, songs are often built around the lyrics. Mostly, the making of a lyric is created from a poem. There are various types of poems, one of it is Tritina. Tritina is the development of the 12th century poem "Sestina" which does not have rhyme but has a repetition algorithm called "circular of sestina". In every work of art, there must be an aesthetic value. Through Monroe Berdsleys theory of aesthetic values, this research wants to examine varieties of tritina literary works in the study of aesthetic theory. This research is a qualitative research with the approach of library research. The result of this study shows that the three main elements of Monroe aesthetic theory namely Unity, Complexity, and Intensity contained in tritina literary works. Using several examples of literary works such as "Living Room" and "Roundstone Cove" written by Marie Ponsot and "A Bowl by Lucie Rie "written by Susan Watson. In Tritina, complexity lies in making the algorithmic system. Intensity in this type of poetry refers to repetition of words or repetitions used. Unity in this work can be seen in the connection between sentences and also the relationship between stanzas. Keywords: Tritina, Sestina, Poetry, Aesthetics, Music